Synergy of Islamic Social Finance and SMEs in Economic Recovery Due to The Covid-19 Pandemic - Isman, Ainul Fatha; Mansir, Amalia Undip Putri; Sidang, Nur Khaerat (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2023)
Background: The existence of MSMEs in Indonesia constitutes the most significant part of the national economy and indicates community participation in various sectors of economic activity. One of the solutions offered in facing the financial crisis is the Islamic social finance sector. Objectives: The research aims to analyze concepts in dealing with the economic crisis caused by the Covid-19 pandemic in Indonesia. Novelty: The novelty of the research contains ideas for SMEs in economic recovery after the Covid-19 pandemic using an Islamic philanthropic approach. Research Methodology / Design: This research method is qualitative descriptive analysis with an inductive reasoning approach through content analysis and library research. Findings: The results of this research show that efforts are needed to recover the economy due to the Covid-19 pandemic by synergizing the concept of philanthropy, namely Zakat, Infaq, Shadaqah, and Waqaf (ZISWAF) with MSMEs, namely optimizing the collection and distribution of ZISWAF funds by implementing GCG (Good Corporate Governance). Collecting digital-based ZISWAF funds, mapping the distribution of regional-based ZISWAF funds, and developing MSMEs by strengthening capital, developing potential businesses, strengthening technology-based MSMEs, and empowering MSMEs based on regional potential.. Implication: Based on the research, this research implications for SMEs in business recovery with various funding innovations and business development models.